Respuesta :

Answer:

2x+7

Step-by-step explanation:

To Simplify an Expression , we combine Like-Terms

So for our Question , we have Terms with x and Constant Term

Combine Terms with x : 5x-2x-x=2x

Constant Term : 7

Then 5x-2x+7-x = 2x+7

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\textbf{Equation: }[/tex]

[tex]\mathbf{5x - 2x + 7 - x = }[/tex] ________[tex]\mathbf{\ x \ + }[/tex]________

[tex]\huge\textbf{Simplify the left side of the equation, to}\\\huge\textbf{get the result of the right side of the}\\\huge\textbf{equation.}[/tex]

[tex]\huge\textbf{Simplifying the LEFT side:}[/tex]

[tex]\mathbf{5x - 2x + 7 - x}[/tex]

[tex]\mathbf{= 5x - 2x + 7 - 1x}[/tex]

[tex]\huge\textbf{Combine the like terms:}[/tex]

[tex]\mathbf{= (5x - 2x - 1x) + (7)}[/tex]

[tex]\mathbf{= 5x - 2x - 1x + 7}[/tex]

[tex]\mathbf{= 3x - 1x + 7}[/tex]

[tex]\mathbf{= 2x + 7}[/tex]

[tex]\huge\textbf{Therefore, your answer should be:}[/tex]

[tex]\huge\boxed{\frak{2\mathsf{x} + 7}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]

ACCESS MORE